Neck Circumference, a Novel Indicator for Hyperuricemia - Jiang, Jiajia; Cui, Jia; Yang, Xinghua; Wang, Anping; Mu, Yiming; Dong, Liguang; Wang, Shuyu; Gaisano, Herbert; Dou, Jingtao; He, Yan (Frontiers in Physiology, 2017)
Background: Waist circumference has been correlated with the risk of hyperuricemia. Whether neck circumference is also associated with hyperuricemia has not been assessed. This study aimed to investigate whether neck circumference is associated with hyperuricemia. Methods: This study population from Beijing is part of the larger China-wide Risk Evaluation of Cancers in Chinese Diabetic Individuals: a lONgitudinal (REACTION) study. For this Beijing sub-center cross-sectional study, a total of 8971 subjects were recruited. Gender-specific multivariable-adjusted regression analyses were conducted to analyze the association of neck circumference and waist circumference with hyperuricemia and the association of neck circumference with serum uric acid levels in the non-hyperuricemia population. Results: After adjusting for confounding variables, regression analyses showed that neck circumference was positively associated with hyperuricemia (OR, 2.61 (1.86-3.67) for males and 3.27 (2.53-4.22) for females) in both genders; further, neck circumference was also positively associated with serum uric acid levels in non-hyperuricemia subjects (b, 2.58 (1.76-3.39) for males and 4.27 (3.70-4.84) for females) in both genders. Additionally, we demonstrated that neck circumference was similar to waist circumference in terms of the strength of association (OR, 3.03 for waist circumference vs. 2.61 for neck circumference in males, and 3.50 vs. 3.27 for females) with hyperuricemia and the ability to predict hyperuricemia (AUC, 0.63 for waist circumference vs. 0.61 for neck circumference in males, and 0.66 vs. 0.66 in females). Conclusion: Neck circumference is positively and independently associated with hyperuricemia in both genders and is also associated with serum uric acid levels in the non-hyperuricemia population.